Assessment of Masks Used by Healthcare Workers: Development and Validation of a Mask Qualitative Assessment Tool (MQAT) - Vahid Gharibi; Rosanna Cousins; Hamidreza Mokarami; Mehdi Jahangiri; Mohammad A. Keshavarz; Mohammad M. Shirmohammadi-Bahadoran (Safety and Health at Work, 2022)
Background: Respiratory masks can provide healthcare workers with protection from biological hazards when they have good performance. There is a direct relationship between the visual specifications of a mask and its efficacy; thus, the aim of this study was to develop tools for qualitative assessment of the performance of masks used by healthcare workers. Methods: A mixed-methods design was used to develop a qualitative assessment tool for medical face masks (MFM) and particle filtering half masks (PFHM). The development of domains and items was undertaken using observation and interviews, the opinions of an expert panel, and a review of texts and international standards. The second phase evaluated the psychometric properties of tools. Finally, the validated Mask Qualitative Assessment Tools (MQAT) were used to assess six samples from 10 brands of the two types of masks. Results: MQAT-MFM and MQAT-PHFM shared 42 items across seven domains: “cleanliness,” “design,” “marking, labeling and packaging,” “mask layers,” “mask strap,” “materials and construction,” and “nose clip.” MQAT-MFM included one additional item. MQAT-PHFM included another nine items associated with an eighth “Practical Performance” domain, and the valve version had another additional “Exhalation Valve” domain and six items. The evaluation indicated 80% compliance for MFM and 71% compliance for PFHM. “Marking, labeling and packaging” and “Layers” were associated with the least compliance in both types of masks and should be checked carefully for defining mask quality. Conclusion: MQAT can be used for immediate screening and initial assessment of MFM and PHFM through appearance, simple tools, and visual inspection.